2014
DOI: 10.1242/jcs.150029
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of Akt isoforms on somatic cell reprogramming

Abstract: Akt plays an important role in cell growth, proliferation and survival. The specific roles of the three Akt isoforms in somatic cell reprogramming have not been investigated. Here we report that, during iPSC generation, enhanced Akt1 activity promotes complete reprogramming mainly through increased activation of Stat3 in concert with leukemia inhibitory factor (LIF) and, to a lesser extent, through promotion of colony formation. Akt1 augments Stat3 activity through activation of mTOR and upregulation of LIF re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…Increased AKT1 phosphorylation is facilitated by the mTORC2 subunit, hence promoting cell proliferation and growth. PTEN , required in maintaining the negative feedback loop mechanism in PI3K/AKT pathway was expressed in all hESCs38. RICTOR and MAPKAP1 , known genes exclusive to mTORC2 subunit39 showed increased expression compared to DEPTOR , a common subunit between mTORC1 and mTORC2 subunits, in the naive lines.…”
Section: Resultsmentioning
confidence: 97%
“…Increased AKT1 phosphorylation is facilitated by the mTORC2 subunit, hence promoting cell proliferation and growth. PTEN , required in maintaining the negative feedback loop mechanism in PI3K/AKT pathway was expressed in all hESCs38. RICTOR and MAPKAP1 , known genes exclusive to mTORC2 subunit39 showed increased expression compared to DEPTOR , a common subunit between mTORC1 and mTORC2 subunits, in the naive lines.…”
Section: Resultsmentioning
confidence: 97%
“…Although the role of PI3K/AKT/mTOR in this process has not been fully uncovered, several reports have demonstrated that PI3K/ AKT signalling promotes iPSC generation through inhibition of GSK3β and FOXO1, while concurrently enhancing the glycolytic metabolism (Silva et al, 2008;Yu et al, 2014;Zhu et al, 2011). This is further supported by experimental evidence indicating that inhibition of AKT hinders somatic cell reprogramming, which is alleviated by the inhibition of GSK3 (Tang et al, 2014).…”
Section: (Box 2)mentioning
confidence: 91%
“…We previously reported Akt isoform-specific knockdown in mouse embryonic fibroblasts (MEFs) using lentiviral shRNA constructs: shAkt1, shAkt2, and shAkt3 (for maximum Akt3 knockdown, shAkt3 consists of two constructs: shAkt3a and shAkt3b targeting different coding regions of Akt3) (Tang et al, 2014). We first tested the effectiveness of these constructs in ESCs.…”
Section: Resultsmentioning
confidence: 99%
“…Akt3 is predominantly activated in a number of cancers such as malignant melanoma and glioma, and plays important roles in the survival of immortalized MEFs (Liu et al, 2006; Mure et al, 2010; Stahl et al, 2004). In a recent study we reported that Akt1 and Akt3 play non-redundant roles in promoting primary MEF cell proliferation during somatic cell reprogramming (Tang et al, 2014), indicating different mechanisms governing cell growth by these two isoforms. One possible mechanism that these Akt isoforms play different functions for cell growth may be through differential cellular localization.…”
Section: Discussionmentioning
confidence: 99%